Prominent Efficacy of Amantadine against Human Borna Disease Virus Infection In Vitro and In Vivo. Comment on Fink et al. Amantadine Inhibits SARS-CoV-2 In Vitro. Viruses 2021, 13, 539 - Liv Bode; Detlef E. Dietrich; Carsten W. Spannhuth; Hanns Ludwig (Viruses, 2022)
Amantadine (1-amino-adamantane) is a versatile antiviral compound which has been licensed for decades against influenza viruses. During the Corona pandemic, its effect to inhibit SARS-CoV-2 in vitro has been investigated. However, an in vivo oral inapplicability was concluded due to ID50 doses exceeding eight times the estimated maximum tolerable plasma levels reached by 600 mg orally daily. In contrast, amantadine has been shown to be extraordinarily efficient against human neurotropic Borna disease virus (BoDV-1), presenting with both anti-depressive and anti-viral efficacy against a placebo, achieved by a well-tolerated low oral daily dose of 200 mg amantadine.